PENERAPAN PENDEKATAN TPACK (TECHNOLOGICAL PEDAGOGICAL CONTENT KNOWLEDGE) UNTUK MENINGKATKAN HASIL BELAJAR PESERTA DIDIK - Fenida Zalukhu; Wahyutra Adilman Telaumbanua; Arianto Lahagu; Eka Septianti Laoli (Jurnal Ilmiah Bina Edukasi, 2025)
This research is based on the results of the researcher's observations during the implementation of the learning process at SMP Negeri 7 Alasa which has so far experienced obstacles in the learning process so that student learning outcomes are relatively low. This study aims to determine the application of the TPACK approach in improving student learning outcomes in Integrated Social Studies subjects in class VII of SMP Negeri 7 Alasa. This type of research is Classroom Action Research (CAR). Based on the results of student observations on student activity activities in cycle I and cycle II, an average of 59.99% and 88.07% was achieved. Then the results of the learning evaluation in cycle I and cycle II reached 64.36% and 81.82%. The percentage of completion achieved in cycle I and cycle II was 53.85% and 92.30%. So it can be concluded that the application of the TPACK (Technological Pedagogical Content Knowledge) approach provides an increase in learning outcomes in Integrated Social Studies subjects in class VII of SMP Negeri 7 Alasa